2013
DOI: 10.1007/s00284-013-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Allelic Variants of the Chromosomal Gene bla OXA-114-like in Achromobacter xylosoxidans Clinical Isolates

Abstract: Achromobacter xylosoxidans is increasingly being documented in cystic fibrosis patients. The bla(OXA-114) gene has been recognized as a naturally occurring chromosomal gene, exhibiting different allelic variants. In the population under study, the bla(OXA-114)-like gene was found in 19/19 non-epidemiological-related clinical isolates of A. xylosoxidans with ten different alleles including 1 novel OXA-114 variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Analysis of HiSeq Illumina data using Galaxy software revealed that isolates from patients A1-A3 were representatives of ST144, while patient A4's isolate differed at all but two of seven loci, representing a novel ST. A search for resistance genes detected a novel bla OXA gene variant. The variant, which was also present in patient A4's isolate (albeit with one base pair difference), was more closely related to the bla OXA-364 variant found in A. dolens (95.3% similarity at the nucleotide level) than to the bla OXA-243e variant found to be associated with A. insuavis 2b (92.0% similarity at the nucleotide level) [10,11].…”
Section: Whole Genome Sequencingmentioning
confidence: 67%
See 1 more Smart Citation
“…Analysis of HiSeq Illumina data using Galaxy software revealed that isolates from patients A1-A3 were representatives of ST144, while patient A4's isolate differed at all but two of seven loci, representing a novel ST. A search for resistance genes detected a novel bla OXA gene variant. The variant, which was also present in patient A4's isolate (albeit with one base pair difference), was more closely related to the bla OXA-364 variant found in A. dolens (95.3% similarity at the nucleotide level) than to the bla OXA-243e variant found to be associated with A. insuavis 2b (92.0% similarity at the nucleotide level) [10,11].…”
Section: Whole Genome Sequencingmentioning
confidence: 67%
“…Intrinsic and acquired resistance in Achromobacter species have been documented, with various carbapenemases described, each of which contributes to the therapeutic challenges associated with these pathogens [5,[8][9][10][11][12]. The intrinsic bla OXA genes reported in the genus, which may not be expressed, are species-specific and are therefore helpful in identification studies [10,11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous PCR-based studies, mostly because they were misguided by the incorrect classification of the genus, present different results regarding allelic variants and the presence of OXA genes in Achromobacter species, and should be treated with caution (Amoureux et al. 2013b; Traglia et al. 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Most Achromobacter clinical isolates are designated as Achromobacter xylosoxidans; however, the commonly used phenotypic tests are not reliable (1)(2)(3). Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) analysis is used in clinical microbiology laboratories as an emerging technology for bacterial species identification (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%